P102. Four-year outcomes of a prospective, controlled, multicenter study evaluating two-level cervical disc arthroplasty with a PEEK-on-ceramic disc - Khalil, Jad G; Guyer, Richard D.; Nunley, Pierce D; Patel, Ashvin I; Park, Andrew E.; Yue, James J.; Khachatryan, Armen; Strenge, K. Brandon; Sasso, Rick C.; Bae, Hyun W. (The spine journal, 2024)
Adoption of cervical disc arthroplasty (CDA) continues to increase. We present the data from the most recently FDA approved device for two-level CDA with PEEK-on-ceramic design. This study evaluated the safety and efficacy of a PEEK-on-ceramic artificial disc implant used in the treatment of 2-level cervical disc disease at 48 months postop. Prospective, nonrandomized, multicenter FDA Investigational Device Exemption (IDE) trial evaluating a PEEK-on-ceramic. Subjects undergoing CDA with 48-month data were included. All patients had 2-level symptomatic cervical disc disease with radiculopathy and/or myelopathy. We evaluated subjects clinically for the following: Neck Disability Index (NDI) score; neurological status; implant, procedure, or implant/procedure associated serious adverse events (SAEs); reoperations; 10-point numeric rating scales assessing neck and arm pain; and patient satisfaction. The study was conducted at 18 sites in the United States. Subjects were evaluated preoperatively, at hospital discharge, at 6 weeks, and at 3, 6, 12, 24, 36, and 48 months after surgery. Forty-eight-month CDA data were compared to preop and 24-month CDA data to assess the durability of results over time. The nonconcurrent historic ACDF control data were not included in the analysis as these data were only available to 24 months. Forty-eight-month data were available for 144 subjects (79.1%). The NDI responder rate (improvement of >15) was 92.9% at 24 months and 94.4% at 48 months. Neck pain responder rates (improvement of ≥2) at 24 and 48 months were 93.0% and 94.9%, respectively; arm pain responder rates were 89.9% and 91.2%, respectively. Mean NDI scores improved from 58.6 preop to 14.3 at 24 months and 14.4 at 48 months (p<0.0001). Neurological status was normal in 93.4% and 94.4% at 24 and 48 months compared to 16.1% preop. Out of the total 182 enrolled subjects, there was a 2.2% rate of implant-related SAEs at 48 months. The procedure-related SAE rate was 2.2% and the rate of SAEs attributed to both implant and procedure was 2.2%. There were an additional five subsequent surgical interventions at the index level between 24 and 48 months (5.0%) compared to four (2.2%) at 24 months. Mean neck pain was 7.9 at preop, 1.8 at 24 months, and 1.8 at 48 months (p<0.0001). Mean arm pain improved from a preop value of 7.5 to 1.8 at 24 months and 1.5 at 48 months (p<0.0001). There were no statistical differences (p>0.05) between 24- and 48-month outcomes for any of the studied variables. At 48 months, 94% of subjects responded Definitely True (88%) or Mostly True (6%) to the statement: "All things considered I would have the surgery again for the same condition.” When asked about their perceived effect of surgical treatment, 94% replied they were “Completely Recovered” (56%) or “Much Improved” (38%). We previously presented 24-month results for PEEK-on-ceramic CDA showing significant improvement in all outcome measures. Results are maintained at 48 months and patients exhibit a high degree of satisfaction. This data is consistent with published mid-term results from other 2-level CDA clinical trials and warrants continued follow up of this patient cohort. Simplify (Approved for this indication).